Analysis of Biochemical and Clinical Pregnancy Loss Between Frozen-Thawed Embryo Transfer of Blastocysts and Day 3 Cleavage Embryos in Young Women: A Comprehensive Comparison - Dai, Xiuliang; Gao, Tingting; Xia, Xiyang; Cao, Fang; Yu, Chunmei; Li, Tianfu; Li, Lingjun; Wang, Yufeng; Chen, Li (Frontiers in Endocrinology, 2021)
Background: To determine whether the embryo developmental stage affects biochemical or clinical pregnancy loss in young women undergoing frozen-thawed embryo transfer (FET) and to investigate the underlying mechanism. Methods: This was a retrospective study including a total of 1834 β-HCG(human chorionic gonadotropin)-positive FET cycles. According to the morphological appearance (MA) of transferred blastocysts, FET cycles with blastocysts were divided into two groups: Group A: morphologically good (MG) blastocysts only, and Group B: at least one morphologically nongood (MNG) blastocyst. FET cycles with day 3 cleavage embryos were assigned as Group C. Biochemical and clinical pregnancy loss were the main outcome measures. Result(s): We predicted 78% in vivo-formed MGs and 53.9% in vivo-formed day 5 blastocysts in Group C. (a) Including cases in Group A and Group B for binary logistic regression, we showed that Group B and day 6 blastocysts had significantly higher rates of BPL and CPL than Group A and day 5 blastocysts, respectively. (b) Including cases in Group A, Group B and Group C for binary logistic regression, we showed that Group C had a significantly higher rate of BPL than Group A and day 5 blastocysts and a similar rate of BPL as Group B and day 6 blastocysts. Group C had a higher rate of CPL than Group A (p=0.071) and day 5 blastocysts (p=0.039), and a lower rate of CPL than Group B (p=0.199) and day 6 blastocysts (p=0.234). Conclusion(s): 1) MA and days of usable blastocysts could serve as independent factors affecting the occurrence of BPL and CPL. 2) Transfer of day 3 cleavage embryos may produce “unusable blastocysts” in vivo, which significantly increased the rate of BPL. 3) The rate of CPL resulting from the transfer of day 3 embryos may depend on the rate of in vivo-formed MG or day 5 blastocysts. Our study indicated that the difference in the BPL or CPL between transfer of blastocysts or day 3 cleavage embryos may largely depend on the quality of embryos transferred.